Есть ли в Украине государственно-политическая традиция? - Балушок, В. (Социология: теория, методы, маркетинг, 1999)
According to the analysis of historical materials, in Ukraine, the state political tradition has been known since Kyiv Rus. It has been related to the Ukrainian political structures of state type and constant political particularity, especially as to foreign policy orientations. On the one hand, this tradition is an obstacle in the way of political centralization and balance of different governmental branches, on the other hand, it contributes to political democratic development.